2018
DOI: 10.3390/rs10101655
|View full text |Cite
|
Sign up to set email alerts
|

Glint Removal Assessment to Estimate the Remote Sensing Reflectance in Inland Waters with Widely Differing Optical Properties

Abstract: The quality control of remote sensing reflectance (R rs ) is a challenging task in remote sensing applications, mainly in the retrieval of accurate in situ measurements carried out in optically complex aquatic systems. One of the main challenges is related to glint effect into the in situ measurements. Our study evaluates four different methods to reduce the glint effect from the R rs spectra collected in cascade reservoirs with widely differing optical properties. The first (i) method adopts a constant coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
(119 reference statements)
0
7
0
Order By: Relevance
“…As the Ibitinga Reservoir is located in the middle portion of Tietê River, it receives hydrological inputs such as non-treated water and surface runoffs from the metropolitan region of São Paulo city ( Bernardo et al 2018 , 2019b ). Its transparency is affected by organic and inorganic waste and pollutants from agricultural, urban and industrial activities in the watershed; the reservoir is characterized as a turbulent and eutrophic reservoir ( Rotta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the Ibitinga Reservoir is located in the middle portion of Tietê River, it receives hydrological inputs such as non-treated water and surface runoffs from the metropolitan region of São Paulo city ( Bernardo et al 2018 , 2019b ). Its transparency is affected by organic and inorganic waste and pollutants from agricultural, urban and industrial activities in the watershed; the reservoir is characterized as a turbulent and eutrophic reservoir ( Rotta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiometric data and water quality parameters data were measured during the fieldwork from 19–23 July 2016 (thirty samples), such as depth, Secchi disk depth, turbidity, pH, chlorophyll-a and reflectance. Details about the data collection protocol and processing can be accessed in Bernardo et al (2018 ; 2019b) and Andrade et al (2018) .…”
Section: Methodsmentioning
confidence: 99%
“…Band combination in NR-2B and Mer-3B could decrease this variability introducing from surface-reflected light (Figure 11c). In addition, it was demonstrated that there is no general value of to be adopted in different inland water conditions, but the most suitable methodology is the spectral , e.g., approach in Lee et al (2010) [69]. However, spectral variability of was not taken into consideration in the process of deriving field-measured R rs (λ), which should be improved in the further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Measured radiance and irradiance (at 3.3 nm resolution) were interpolated to 1 nm resolution [38,39]. The R rs variable was calculated using the spectral glint removal method [40], which is considered the most reliable [41]. We measured the particulate absorbance using a dual-beam UV-2600 UV-VIS spectrophotometer (SHIMADZU, Japan) at 1 nm resolution, over 280 to 800 nm.…”
Section: Fieldsite and Datasetmentioning
confidence: 99%